Given the following system of equations:
-8x + 5y = -23
-8x - 9y = 19
Let's determine the solution by Elimination:
-8x + 5y = -23
(-) -8x - 9y = 19
-8x + 5y = -23
+ 8x + 9y = -19
0 + 14y = -42
14y/14 = -42/14
y = -3
Let's now determine the value of x by substituting y = -3 in -8x - 9y = 19.
-8x - 9y = 19
-8x - 9(-3) = 19
-8x + 27 = 19
-8x = 19 - 27
-8x = -8
-8x/-8 = -8/-8
x = 1
Therefore, the solution is x = 1 and y = -3 or (1,-3). We can also say that the graph of the two equations intersects at (1,-3).